Influence Of The Use Of Interactive Learning Media On Students’ Higher Order Thinking Skills - Rizkyamana Nur Chasanah; Mujasam Mujasam; Sri Wahyu Widyaningsih; Irfan Yusuf (Kasuari: Physics Education Journal (KPEJ), 2019)
The research aims to find out the influence of using interactive learning media on students’ higher order thinking skills. This research use a type of quasi experimental with a time series design form. Research objects were students from class XII IPA SMA Yapis Manokwari and numbered 19 people. Data analysis requirements show that the data are normally distributed but not homogeneous so the research data is tested using the wilcoxon test. The decision making results were based on Asymp. Sig. (2-tailed) in the amount of 0,014 < α = 0,05 so that the hypothesis of H0 was rejected or Ha was accepted. This means that there is the influence of the used of interactive learning media on students’ higher order thinking skills. The result of the N-gain test calculation show that there is an effect of increasing higher order thinking skills which are at intervals g < 0,3, which is equal to 0,2 that include in low category. The acquisition of an effect size value in the amount of 0,06 which is in the interval d < 0,2 indicates that the effectiveness of interactive learning media in improving higher order thinking skills is in a small category. Students’ higher order thinking skills can be seen from the average score in completing higher order thinking cognitive tests, which amounted to 32,64 (posttest 1) in the low category, 37,58 (posttest 2) in the low category and 38,97 (posttest 3) in the low category. This value means that the use of interactive learning media has a low influence on improving students’ higher order thinking skills. This is also supported by the results of the perception questionnaire analysis which shown the P2b statement is difficult to approve with the highest logit value of +2. This means that students assume that interactive learning media is difficult to use and less flexible.